BS EN 4842. Aerospace series. Steel X5CrNiCu15-5 (WL 1.4545). Consumable electrode remelted (ESR or VAR). Solution treated and precipitation treated (H1025). Bars for machining. a or D ≤ 250 mm. 1 070 MPa ≤ Rm ≤ 1 200 MPa. Premium quality (pq). (15th September 2020) - British Standards Institution,
No abstract available